2021
DOI: 10.1016/j.jrurstud.2020.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Becoming citizens: Policy feedback and the transformation of the Thai rice farmer

Abstract: Over the past twenty years, Thailand's rice farmers have become one of the country's most important and active political constituencies, a sharp contrast from the previous decades wherein they were treated with neglect or even derision by the Thai political elite. These "political peasants" now actively advocate for and successfully receive extensive subsidies from both authoritarian and democratic governments. What has driven this change? In this essay, we draw on theories of the policy feedback loop wherein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…Moreover, agricultural policies have been traditionally designed in Thailand in a top-down way, even those geared towards capturing farmers’ votes (Ricks and Laiprakobsup 2021 ). Walker’s ( 2012 ) detailed assessment of the relationship between farmers and public actors in the Northern Region of Thailand showed that these relations were aimed at organising flows of resources to support farms.…”
Section: Thai Farms: Many Challenges Few Explored Futuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, agricultural policies have been traditionally designed in Thailand in a top-down way, even those geared towards capturing farmers’ votes (Ricks and Laiprakobsup 2021 ). Walker’s ( 2012 ) detailed assessment of the relationship between farmers and public actors in the Northern Region of Thailand showed that these relations were aimed at organising flows of resources to support farms.…”
Section: Thai Farms: Many Challenges Few Explored Futuresmentioning
confidence: 99%
“…There was no room for discussing challenges facing the farms and how to best address them. Moreover, Ricks and Laiprakobsup ( 2021 ) argued that policy implementation can produce lock-ins, in the sense that they frame actors’ expectations about what state intervention should be. They showed that Thai rice farmers’ request for support on rice prices was an upshot of the prevailing policies, thereby pushing discussion on more structural issues into the background.…”
Section: Thai Farms: Many Challenges Few Explored Futuresmentioning
confidence: 99%
“…The vast majority of small-scale farmers are located in the Northeast and North regions (83.23 and 77.63%, respectively) (OAE, 2019). This sector has experienced successive policy interventions ranging from low-interest loans to rice farmers to fixed higher-than-market price for paddy rice (Poapongsakorn and Pantakua, 2014; Ricks and Laiprakobsup, 2021). Four main marketing channels for paddy rice have been used by rice farmers in Thailand (Srisompun, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, central paddy markets, established in 1980, had a market share of nearly 24% by 1997 (Isvilanonda, 2010) due to the fact that the initial RPS was implemented by the Bank for Agriculture and Agricultural Cooperatives which operated in central paddy markets. However, the RPS introduced in 2011 favored rice millers more (Ricks and Laiprakobsup, 2021). By 2013, the share of central paddy markets dropped by nearly half to 12.59% (Srisompun, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation